2014
DOI: 10.1182/blood.v124.21.391.391
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography (PET) Guided Therapy of Aggressive Lymphomas – a Randomized Controlled Trial Comparing Different Treatment Approaches Based on Interim PET Results (PETAL Trial)

Abstract: Introduction: The predictive value of 18-fluorodeoxyglucose PET performed after a few cycles of chemotherapy has been questioned in aggressive lymphomas. Inconsistent study results, however, may be due to procedural differences rather than an inability of the method to predict outcome. Whether changing treatment in pts. with an unfavorable interim PET (iPET) improves outcome, has not been determined in a randomized study. The PETAL trial (EudraCT 2006-001641-33, NCT00554164) was initiated to resolve these issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…Interim PET has been evaluated as a possible biomarker of early R‐CHOP success or failure in several retrospective and prospective studies. About 39–87% patients achieve a negative interim FDG‐PET/CT in prospective studies of advanced stage DLBCL initially receiving R‐CHOP, as shown in Table . The rate of interim FDG‐PET/CT negativity is very broad due to significant heterogeneity between studies, including variable timing of the interim PET (after 2, 3, or 4 cycles) as well as variable interpretation criteria with different definitions of FDG‐PET/CT positivity (internal visual point systems, International Harmonization Project criteria, Deauville criteria).…”
Section: Interim Fdg‐pet/ct Response Adapted Treatment Strategiesmentioning
confidence: 99%
“…Interim PET has been evaluated as a possible biomarker of early R‐CHOP success or failure in several retrospective and prospective studies. About 39–87% patients achieve a negative interim FDG‐PET/CT in prospective studies of advanced stage DLBCL initially receiving R‐CHOP, as shown in Table . The rate of interim FDG‐PET/CT negativity is very broad due to significant heterogeneity between studies, including variable timing of the interim PET (after 2, 3, or 4 cycles) as well as variable interpretation criteria with different definitions of FDG‐PET/CT positivity (internal visual point systems, International Harmonization Project criteria, Deauville criteria).…”
Section: Interim Fdg‐pet/ct Response Adapted Treatment Strategiesmentioning
confidence: 99%
“…Interim PET‐CT has been shown to provide prognostic value . In the PETAL trial, 13% of patients had FDG avidity at interim PET‐CT which was associated with dismal long‐term outcome . To date, no strategy of intensification or alternative therapy has improved the outcome for patients with positive interim PET‐CT findings.…”
Section: Blinatumomabmentioning
confidence: 99%
“…PET/CT-based evaluation of response to cancer treatment has proved a reliable outcome predictor in several tumours [2][3][4]. Quantitative metrics for PET/CT scan (Q-PET) interpretation by Standardized Uptake Value (SUV) have been recently shown to improve the prognostic role of PET both at baseline and during treatment [3,5], but only few prospective clinical trials are underway using these metrics for PET/CT scan interpretation [6]. Besides more sophisticated approaches [7] and taking in account its intrinsic limitations [8], SUV is being universally used as a measure of tumour viability by itself or mixed up with more complex indexes [9].…”
Section: Introductionmentioning
confidence: 99%